Program “Happy HAKI” for Sustainable Economics Development - Shilvina Widi Irsanti (Bappenas Working Papers, 2019)
Happy HAKI is an association of industrial products businesses that have the original one and deserves to be given HAKI. This program under the auspices of the industry trade and sme. Basically a form of “Happy HAKI” as arisan in general the perpetrators UMKM will turn in compulsory payments of every month and will draw straws who will get HAKI.